2020
DOI: 10.30534/ijeter/2020/47862020
|View full text |Cite
|
Sign up to set email alerts
|

3-D modelling and 3-D printing in design and manufacturing of optical sensors

Abstract: The main purpose of the study is an optimization of design and manufacturing technologies in application to optical sensors, defining the phase composition of different liquids. The sensors use effects of phase contrast and speckle interferomerty so the demands to precision and stability of their optical path geometry are very high. Special attention is paid to chemical composition of filaments in order to avoid dissolution and deformation of 3-D printed parts under contact with aggressive solvents and liquids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Design and customization experts (Choonara et al , 2016; Mobbs et al , 2017) and high-skilled data analysts (Cacciamani et al , 2019; Sahoo et al , 2020) can help the supply chain to overcome the problems of medical model accuracy (Tappa and Jammalamadaka, 2018; Asmaria et al , 2020). Our findings revealed that limited materials options (Liu et al , 2020; Alkhaibary et al , 2020), slow production speed (Pietrzak et al , 2015; Pavlov and Valkov, 2020), manual post-processing (Hirsch et al , 2020), high-skilled data analyst (Cacciamani et al , 2019; Sahoo et al , 2020) and simulation accuracy (Gibson et al , 2012; Tel et al , 2020) are the key driving factors for the 3DPMM supply chain, which find support from the literature.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Design and customization experts (Choonara et al , 2016; Mobbs et al , 2017) and high-skilled data analysts (Cacciamani et al , 2019; Sahoo et al , 2020) can help the supply chain to overcome the problems of medical model accuracy (Tappa and Jammalamadaka, 2018; Asmaria et al , 2020). Our findings revealed that limited materials options (Liu et al , 2020; Alkhaibary et al , 2020), slow production speed (Pietrzak et al , 2015; Pavlov and Valkov, 2020), manual post-processing (Hirsch et al , 2020), high-skilled data analyst (Cacciamani et al , 2019; Sahoo et al , 2020) and simulation accuracy (Gibson et al , 2012; Tel et al , 2020) are the key driving factors for the 3DPMM supply chain, which find support from the literature.…”
Section: Resultssupporting
confidence: 76%
“…3D printing’s production speed is slow and unsuitable for high volume production. Experts need to develop high production speeds to support more patient-specific cases without compromising mechanical strength, surface finishing and dimensional accuracy (Pietrzak et al , 2015; Pavlov and Valkov, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation